IMPLEMENTATION OF PENTAHELIX FRAMEWORK ON THE DEVELOPMENT OF PUJON KIDUL TOURISM VILLAGE, PUJON DISTRICT, MALANG REGENCY - Nirwikara Widhiwidhana Prasetyanto; Lucyana Trimo; Iwan Setiawan (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Tourism village can be definied as a combination of accommodation, attractions and supporting facilities that are integrated with the life, traditions and local wisdom of rural communities. The development of tourist villages is a form of community-based tourism. The development of a tourist village needs synergy and collaboration from various stakeholders. This study aims to explain the role of stakeholders within the Pentahelix framework in the development of community-based agro-tourism in the Pujon Kidul Tourism Village, Pujon District, Malang Regency that never mentioned yet in previous research by using Miles and Huberman interactive model. The results of the study show that the stakeholders involved in tourism development in Pujon Kidul Village are academics (Universities and the Smart Village Foundation), business (BUMDes Sumber Sejahtera, travel agents and BNI Bank), community, government and the media. Academics play a role in research, development and community empowerment. Businesses, especially BUMDes Sumber Sejahtera, play a role in managing various tourism business units. The community acts as the main actor in tourism management. The government plays the role of planner, policy maker and promotes investment. The media plays a role in helping the promotion of tourist destinations in Pujon Kidul Village. The suggestion that needs to be done is to give priority to the community within the pentahelix framework In order for the community to be capable of becoming the main actor of development of Pujon Kidul tourism village.